Motivational analyses of social behavior : building on Jack Brehm's contributions to psychology - Wright, Rex A.; Greenberg, Jeff; Brehm, Sharon S. (Lawrence Erlbaum, 2004)
In honour of Jack Brehm's contributions to contemporary psychology, this volume revolves around the focus of most of his work - motivation and emotion in social context. It demonstrates Brehm's enormous influence on the field by highlighting how others have taken his ideas and expanded upon them.